2020
DOI: 10.1001/jamanetworkopen.2020.30932
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Machine Learning Model Using Multiple, Heterogeneous Data Sources to Estimate Weekly US Suicide Fatalities

Abstract: IMPORTANCE Suicide is a leading cause of death in the US. However, official national statistics on suicide rates are delayed by 1 to 2 years, hampering evidence-based public health planning and decision-making. OBJECTIVE To estimate weekly suicide fatalities in the US in near real time. DESIGN, SETTING, AND PARTICIPANTSThis cross-sectional national study used a machine learning pipeline to combine signals from several streams of real-time information to estimate weekly suicide fatalities in the US in near real… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 40 publications
0
29
0
Order By: Relevance
“…However, prior research has indicated that it is still prudent to attempt to combine information from these alternative signals with traditional sources to improve both performance and reliability of the model. 14 Although this approach to predicting opioid overdose deaths demonstrated promise, much additional work remains. Although we validated our approach over 2 separate years, future prospective validation is an ongoing need.…”
Section: Limitationsmentioning
confidence: 99%
“…However, prior research has indicated that it is still prudent to attempt to combine information from these alternative signals with traditional sources to improve both performance and reliability of the model. 14 Although this approach to predicting opioid overdose deaths demonstrated promise, much additional work remains. Although we validated our approach over 2 separate years, future prospective validation is an ongoing need.…”
Section: Limitationsmentioning
confidence: 99%
“…Some helplines specialize in particular issues such as suicide, children or violence against women. Suicide helplines, for example, have been shown to reduce suicide rates 13 , and call volumes of suicide prevention helplines have been shown to relate to the incidence of actual suicides 14 .…”
mentioning
confidence: 99%
“…Lifeline have been used to predict the incidence of actual suicides, e.g. by [12]. As a helpline focused on suicide, however, the Lifeline does not allow us to track changes in the composition of mental health problems.…”
Section: Resultsmentioning
confidence: 99%